Improved Anti-Atopic Dermatitis Effect of H. macrophylla through the Generation of Hydrangenol by Microwave Processing - Kim, Youngseok; Ju, Ha-Neul; Choi, Pilju; Kim, Taejung; Park, Young-Tae; Lee, Dae-Hee; Ham, Jungyeob (ACG Publications, 2022)
The compounds hydrangenol and hydrangenol 8-O-glucoside are abundant in Hydrangea macrophylla. This study investigated the effects of hydrangenol and hydrangenol 8-O-glucoside derived from H. macrophylla on atopic dermatitis (AD). Compared with hydrangenol 8-O-glucoside, hydrangenol resulted in more potent inhibition of interleukin 4 (IL-4) gene expression and beta-hexosaminidase release, as well as more potent inhibition of the phosphorylation of signal transducer and activator of transcription 6 (STAT6). Ultra High-Performance Liquid Chromatography (UHPLC), the concentrations of hydrangenol were found to be lower than the concentration of hydrangenol 8-O-glucoside in H. macrophylla extracts. To increase the hydrangenol content of H. macrophylla extract, component conversion methods were studied. Conclusion, microwave processing was found to be the optimal method for deglycosylation.